Northern Shrimp (Pandalus borealis) Stock on Flemish Cap According to 1988-1996 surveys - Río-Iglesias, José Luis del; Sainza-Sousa, María del Carmen (1997)
Shrimp was regularly caught in Flemish Cap bottom trawl surveys from 1988 to 1996. Sampling results were previously published: Escalante et al., 1990; Mena, 1991-1992; Sainza, 1993a-1993b-1994-1995 and del Rio, 1996. The whole information is now reviewed to document the evolution of the stock abundance and structure during the period. This was a singular time period because of the active fishery started in April 1993.